"That City Af loat": Maritime Dimensions of Ireland's Great Famine Migration. Issue 1 (26th April 2022) - McMahon, Cian T
Abstract: Throughout the eighteenth and nineteenth centuries, millions of migrants from every corner of the earth spent weeks and sometimes months at sea. Yet these ubiquitous voyages appear as little more than blank pages in the annals of human migration. Maritime social history has grown considerably over the past thirty years, offering brilliant new insights into the lived experiences of sailors, pirates, and slaves. But the lowly emigrant has been largely ignored. At the same time, scholars carefully tracing the development of migrant communities at the local, national, and transnational levels have tended to reify the historiography's traditional terracentrism. Using the letters, diaries, and printed guides of those who left Ireland during the Great Famine, this article seeks to understand how the journey itself shaped community building in the Irish diaspora. It argues that the hardships of life at sea encouraged disparate groups of people to expand their traditional ideas of belonging. Localism and ethnic identity did not dissolve at sea, they changed—making room for new and heterogeneous links of solidarity anchored in shared experience.